UTP14A, DKC1, DDX10, PinX1, and ESF1 Modulate Cardiac Angiogenesis Leading to Obesity-Induced Cardiac Injury - Xiaoyu Pan; Shuchun Chen; Xing Chen; Qingjuan Ren; Lin Yue; Shu Niu; Zelin Li; Ruiyi Zhu; Xiaoyi Chen; Zhuoya Jia; Ruoxi Zhen; Jiangli Ban (Journal of Diabetes Research)
Background. This study is aimed at exploring the key genes and the possible mechanism of heart damage caused by obesity. Methods. We analyzed the GSE98226 dataset. Firstly, differentially expressed genes (DEGs) were identified in heart tissues of obese and normal mice. Then, we analyzed DEGs using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis. Thirdly, we constructed a protein-protein interaction (PPI) network and key modules and searched hub genes. Finally, we observed the pathological changes associated with obesity through histopathology. Results. A total of 763 DEGs were discovered, including 629 upregulated and 134 downregulated genes. GO enrichment analysis showed that these DEGs were mainly related to the regulation of transcription, DNA-templated, nucleic acid binding, and metal ion binding. KEGG pathway analysis revealed that the DEGs were enriched in long-term depression, gap junction, and sphingolipid signaling pathways. Finally, we identified UTP14A, DKC1, DDX10, PinX1, and ESF1 as the hub genes. Histopathologic analysis showed that obesity increased the number of collagen fibers and decreased the number of microvessels and proliferation of the endothelium and increased endothelial cell damage which further leads to dysfunction of cardiac microcirculation. Conclusion. UTP14A, DKC1, DDX10, PinX1, and ESF1 have been identified as hub genes in obesity-induced pathological changes in the heart and may be involved in obesity-induced cardiac injury by affecting cardiac microcirculatory function.